Australian species of the genus Agapetus (Trichoptera: Glossosomatidae), with descriptions of 13 new species - Wells, Alice (Zootaxa, 2010)
The genus Agapetus Curtis (Trichoptera: Glossosomatidae) in Australia is reviewed. Among the 23 species recognised, 13 are newly described: Agapetus cannensis sp. nov., A. christineae sp. nov., A. dundungra sp. nov., A. mittamitta sp. nov., A. mossmanensis sp. nov., A. muelleri sp. nov., A. neboissi sp. nov., A. paluma sp. nov., A. paracralus sp. nov., A. sheldoni sp. nov., A. stclairae sp. nov., A. tubrabucca sp. nov., A. zwicki sp. nov. Australian species occur mainly in the streams of Tasmania and of the Great Dividing Range on the mainland. Diagnostic characteristics and the known distribution for each Australian species are discussed briefly and a key to males of Australian species is provided.